Experimental Investigation of the Periodic Unsteady Transonic Flow Field Around a Compressor Blade by Means of Particle Image Velocimetry (PIV) - A. Lehr; A. Bölcs (International Journal of Rotating Machinery)
In the present article, a study of the time-dependent transonic flow field around an isolated airfoil in a Laval nozzle is presented. In order to obtain instantaneous flow field information all over the flow around the blade, the Particle Image Velocimetry (PIV) method has been employed allowing one to obtain velocity data in an illuminated light sheet with a high data acquisition rate and high spatial resolution. From these instantaneous PIV measurements the mean velocity field and turbulence quantities of the flow easily can be obtained by statistical means.